The Construction of Work Readiness Scale - Farenanda Kusuma Wardani; Afifudin Isnain; Anggi Nur Alifah; Putri Uswatun Khasanah; Farica Ayu Nabila; Shavira Ika P; Hemalia Astikawati; Aftina Nurul Husna (Prosiding University Research Colloquium, 2021)
Fresh graduates are human resources that determine the sustainability of anorganization/company. Psychologically, they should have mature work readiness beforeentering the world of work. This study aims to develop a work readiness scale for freshgraduates. Psychological work readiness is defined as the extent to which graduates areperceived to have the attitudes and attributes that make them ready to succeed in the workenvironment. This scale contains four aspects that support the form of self-readiness forthe world of work, namely resilience/resilience, maturity/maturity, motivation, andinterpersonal skills. Participants in this study were 61 fresh graduates of Bachelor andDiploma programs in all majors with a graduation period of 2019-2021 and not yetworking. The data collection method used is the saturation sampling and snowballsampling technique. The data were analyzed for validity and tested for reliability with theSPSS program. Of the 72 items tested, 24 final items were obtained with an alphareliability of 0.938 and showed good validity. The work readiness scale for fresh graduateshas good psychometric properties and can be used for assessment and research.